ANALISIS KUALITAS LAYANAN SERVICE TERHADAP TINGKAT KEPUASAN PENGGUNA MOTOR SUZUKI PADA BENGKEL PT SINAR GALESONG PRATAMA MAKASSAR - Abner Tahendrika (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2015)
The objective of this research is to analyze the impact of service quality, including, tangible, reliability, responsiveness, assurance and empathy toward customer satisfaction at bengkel PT Sinar Galesong Pratama Makassar. This research used quantative research design. Multiple linear regression analysis used in this reserach. The results show that the service quality significantly influences to customer satisfaction and the variables of service quality which have the most influence on customer satisfaction are tangible variable.